The effects of upper airway tissue motion on airflow dynamics. (23rd January 2020) - Zhao, Yongling; Raco, Joel; Kourmatzis, Agisilaos; Diasinos, Sammy; Chan, Hak-Kim; Yang, Runyu; Cheng, Shaokoon
Abstract: The human upper airway is not only geometrically complex, but it can also deform dynamically as a result of active muscle contraction and motility during respiration. How the active transformation of the airway geometry affects airflow dynamics during respiration is not well understood despite the importance of this knowledge towards improving current understanding of particle transport and deposition. In this study, particle imaging velocimetry (PIV) measurements of the fluid dynamics are presented in a physiologically realistic human upper airway replica for (i) the undeformed case and (ii) the case where realistic soft tissue motion during breathing is emulated. Results from this study show that extrathoracic wall motion alters the flow field significantly such that the fluid dynamics is distinctly different from the undeformed airway. Distinctive flow field patterns in the physiologically realistic airway include (i) fluid recirculation at the back of the tongue and cranial to the tip of the epiglottis during mid-inspiration, (ii) horizontal and posteriorly directed flow at the back of tongue at the peak of inspiration and (iii) a more homogeneous flow across the airway downstream from the epiglottis. These findings suggest that the active deformation of the human upper airway may potentially influence particle transport and deposition at the back of the tongue and therefore, highlights the importance of considering extrathoracic wall motion in future airway flow studies. D.